TRANSHUMANISM AND THE ETHICS OF THE POSTHUMAN IN THE CONTEXT OF SPACE EXPANSION - Oleshchenko, Volodymyr (The Journal of V. N. Karazin Kharkiv National University, Series Philosophy. Philosophical Peripeteias, 2025)
This article examines the philosophical foundations of transhumanism in the context of humanity’s potential expansion beyond Earth. The posthuman subject is examined as one shaped by technological modifications, artificial intelligence, mind-machine interfaces, and the extreme conditions of extraterrestrial environments. In this framework, space is not only a physical frontier but a platform for radically rethinking the human condition.            The author considers transhumanism not as a futurist utopia but as an ethical practice that transforms the relationships between embodiment, technology, and morality. The article introduces conceptual tools such as adaptive subjectivity, moral recalibration, and cognitive modification within the framework of interstellar existence. Particular attention is paid to the problem of preserving moral continuity amid radical alterations of corporeality, as well as to forms of cooperation between humans and non-anthropomorphic agents in autonomous off-Earth communities.            The article offers a critical examination of limit-case scenarios, including bodily deconstruction, consciousness emulation, and the emergence of algorithmic instances endowed with moral responsibility. The focus is not primarily on technologies themselves, but on the ontological shifts they trigger in how we understand freedom, autonomy, and the boundaries of the subject. The study lays the groundwork for a posthuman ethics applicable to extreme future environments in which core categories of humanism lose their intuitive self-evidence.